Abul Kalam Azad’s idea of religious pluralism for an inclusive Indian nationalism: a civilizational revisit - Ali, Md Yousuf; Bakar, Osman (IIUM Press, 2023)
Abul Kalam Azad (1888-1958), the first Minister of Education in independent India, was a towering figure in the modern subcontinent. A freedom fighter against British colonial rule following the steps of Syed Ahmad Khan (1817-1898), an Islamic thinker, and a champion of Hindu-Muslim unity, Azad was an intellectual-activist advocating an inclusive Indian nationalism. This article focuses on Azad’s idea of religious pluralism based on the doctrine of unity of religions (wahdat al-adyan) and how he related it to his vision of an inclusive Indian nationalism. It discusses the main ideas embodied in this vision, especially the interrelated ideas of national unity and integrity, communal solidarity and harmony, cultural cohesion, and the need for a comprehensive education system that would serve national unity and the well-being of all Indians. Azad’s idea of unity of religions is articulated in his well-known exegetical work The Tarjuman al-Qur’an, especially in his commentary on the “Opening Chapter” (Surah al-Fatihah) of the Qur’an. This article also shows that Azad emphasized on common religious and cultural values as a means of embracing others for partnership in a national unity movement.